2013
DOI: 10.3892/or.2013.2945
|View full text |Cite
|
Sign up to set email alerts
|

The heme precursor 5-aminolevulinic acid disrupts the Warburg effect in tumor cells and induces caspase-dependent apoptosis

Abstract: Abstract. Our previous study demonstrated that 5-aminolevulinic acid (ALA) administered to mice stimulates oxidative phosphorylation by upregulation of the mitochondrial respiratory chain complex IV enzyme cytochrome c oxidase (COX). The present study investigated whether ALA disrupts the Warburg effect, which represents a shift in ATP generation from oxidative phosphorylation to glycolysis, protecting tumor cells against oxidative stress-mediated apoptosis. The human lung carcinoma cell line A549 exposed to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
(25 reference statements)
2
19
0
Order By: Relevance
“…The biological effect of administration of the heme precursor 5-ALA is not only high accumulation of PpIX within the mitochondria of tumor cells, but also generation of antitumor immunity via activation of heat-shock protein as well as inhibition of heme-oxygenase-1 with photoactivation and hyperthermia (26). Moreover, recent studies have reported that 5-ALA can improve the function of the mitochondrial respiratory chain (particularly COX activity) and thereby disrupt the warburg effect and induce caspase-dependent apoptosis in tumor cells (27,28). In our previous study, we demonstrated that multi-dose ionizing radiation induced strong aggregation of activated macrophages with phagocytic features within tumors, causing strong inhibition of tumor growth in glioma cells in vivo (19).…”
Section: -Ala Acts As a Radiosensitizer Via The Enhancement Of Delaymentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effect of administration of the heme precursor 5-ALA is not only high accumulation of PpIX within the mitochondria of tumor cells, but also generation of antitumor immunity via activation of heat-shock protein as well as inhibition of heme-oxygenase-1 with photoactivation and hyperthermia (26). Moreover, recent studies have reported that 5-ALA can improve the function of the mitochondrial respiratory chain (particularly COX activity) and thereby disrupt the warburg effect and induce caspase-dependent apoptosis in tumor cells (27,28). In our previous study, we demonstrated that multi-dose ionizing radiation induced strong aggregation of activated macrophages with phagocytic features within tumors, causing strong inhibition of tumor growth in glioma cells in vivo (19).…”
Section: -Ala Acts As a Radiosensitizer Via The Enhancement Of Delaymentioning
confidence: 99%
“…This delayed ROS production is induced primarily in the mitochondria of tumor cells (24,25). Meanwhile, the heme precursor 5-ALA presents not only a high accumulation of PpIX in the mitochondria of tumor cells, but also improves dysfunction of the mitochondrial respiratory chain in tumor cells (26)(27)(28). Thus, we hypothesized that 5-ALA-induced PpIX may operate upon mitochondria, and cause changes in delayed production of ROS after ionizing irradiation in tumor cells.…”
Section: -Aminolevulinic Acid Strongly Enhances Delayed Intracellulamentioning
confidence: 99%
“…We previously reported that the expression and activity of the hemeprotein cytochrome c oxidase is elevated in ALA-treated cells [ 11 , 12 ]. Moreover, we found that the expression of PEPT1, a transporter involved in the uptake of ALA, is higher in tumor tissues compared with that in normal tissues [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injection of ALA induced expression and activity of COX in mice liver [22]. It also enhanced COX expression and oxygen consumption in a lung cancer cell line, A549 [23]. Accordingly, we expected that regulation of heme synthesis using ALA, SFC, and SA should affect mitochondrial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the fact that COX is a heme protein, ALA-mediated increase in the amount of heme was thought to induce the expression COX. We also reported that addition of ALA leads to activation of ETS in cancer cells [23].…”
Section: Introductionmentioning
confidence: 99%